Brain Gαi2-subunit proteins and the prevention of salt sensitive hypertension - Carmichael, Casey Y.; Wainford, Richard D. (Frontiers in Physiology, 2015)
To counter the development of salt-sensitive hypertension multiple brain G-protein–coupled receptor (GPCR) systems are activated to facilitate sympathoinhibition, sodium homeostasis and normotension. Currently there is a paucity of knowledge regarding the role of down-stream GPCR-activated Gα-subunit proteins in these critically important physiological regulatory responses required for long-term blood pressure regulation. We have determined that brain Gαi2-proteins mediate natriuretic and sympathoinhibitory responses produced by acute pharmacological (exogenous central nociceptin/orphanin FQ receptor and α2-adrenoceptor activation) and physiological challenges to sodium homeostasis (intravenous volume expansion and 1M sodium load) in conscious Sprague-Dawley rats. We have demonstrated in salt-resistant rat phenotypes, high dietary salt intake evokes site-specific up-regulation of hypothalamic paraventricular nucleus (PVN) Gαi2–proteins. Further, we established that PVN Gαi2 protein up-regulation prevents the development of, renal nerve-dependent sympathetically mediated salt-sensitive hypertension in Sprague-Dawley and Dahl salt-resistant rats. Additionally, failure to up-regulate PVN Gαi2 proteins during high salt-intake contributes to the pathophysiology of Dahl salt-sensitive hypertension. Collectively, our data demonstrate that brain, likely PVN specific, Gαi2 protein pathways represent a central molecular pathway mediating sympathoinhibitory renal-nerve dependent responses evoked to maintain sodium homeostasis and a salt-resistant phenotype. Further, impairment of this endogenous “anti-hypertensive” mechanism contributes to the pathophysiology of salt-sensitive hypertension.